Studying argumentation and education in South America: what has been advanced and what lies ahead. (2nd October 2022) - Fortes, Gabriel; Guzmán, Valentina; Larrain, Antonia
ABSTRACT: With this paper, we aim to present what has been developed so far in the field of argumentation and education in South America to the best of our knowledge. However, we also aim to anticipate new trends that will arise from the challenges South American democracies face right now, and the role of collective reasoned discussion in tackling them. Traditionally argumentation studies have been proposed within three broad areas of research and practice. First, argue to learn, as the uses of argumentation practices to develop conceptual knowledge in different domains of education. Second, learn to argue by promoting argumentative practices to develop argumentative and thinking skills. Third, teacher professional development enables teachers to enact argumentation in their classrooms. From this scenario, we argue that three interrelated branches of research are the future ahead of us: studies of argumentation and citizen education using deliberative practices, cultivating virtuous intellectual habits, and the rise of deliberative teaching focused on collaborative settings designed to empower democratic values (diversity, equality, and participation). We conclude by stating that South America has helped the advancement of argumentation theory, but we still have a road ahead in developing more spaces for democratic participation.